2008
DOI: 10.1155/2008/235461
|View full text |Cite
|
Sign up to set email alerts
|

Early Expression of FcγRI (CD64) on Monocytes of Cardiac Surgical Patients and Higher Density of Monocyte Anti‐Inflammatory Scavenger CD163 Receptor in “On‐Pump” Patients

Abstract: Objective. Activation of innate immunity cells is inseparably linked to cardiac surgical operation. The aim of this study was to assess the kinetics in the expression of receptor for Fc part of IgG, FcγRI (CD64), and scavenger receptor CD163 on peripheral blood cells of cardiac surgical patients and to examine the effect of cardiac bypass as a separable influence on the systemic acute inflammatory response. Methods. Forty patients, twenty in each group, were randomly assigned to CABG surgery performed either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 23 publications
7
25
0
Order By: Relevance
“…We could not fine a statistically difference in monocyte CD64 dynamics pattern by a subgroup of patients (n=8), who developed postoperatively SIRS associated with infections. These results correspond well with earlier report [5], and indicate that activation of CD64 on monocytes is a more unspecific phenomenon than "de novo" synthesis of this receptor on neutrophils. It also confirms the conclusion that in the presence of proinflammatory stimuli the upregulation of CD64 on monocytes and neutrophils at least are regulated by different mechanisms [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We could not fine a statistically difference in monocyte CD64 dynamics pattern by a subgroup of patients (n=8), who developed postoperatively SIRS associated with infections. These results correspond well with earlier report [5], and indicate that activation of CD64 on monocytes is a more unspecific phenomenon than "de novo" synthesis of this receptor on neutrophils. It also confirms the conclusion that in the presence of proinflammatory stimuli the upregulation of CD64 on monocytes and neutrophils at least are regulated by different mechanisms [11].…”
Section: Discussionsupporting
confidence: 93%
“…All three receptors have been investigated by leukocytes in different study design by different patient's groups. The key goal was either to identify patients at the risk of development of overwhelming inflammatory response or to implicate the causative agent of such a response, for example, bacterial infection [5][6][7]. In a previous study we found neutrophil CD64 expression to be a specific marker for the detection of bacterial infections after a major surgical trauma [8].…”
Section: Introductionmentioning
confidence: 99%
“…It represents a new class of macrophage specific biomarkers relevant to the detection of coronary artery disease, transplantation, atherosclerosis, rheumatoid arthritis, lysosomal Gaucher storage diseases and cancer, cardiac surgery patient respectively (4,15).…”
Section: Soluble Form Of Cd163 (Scd163)mentioning
confidence: 99%
“…In many of this diseases, the patients are extensively exposed to a large amounts of free heme/hemoproteins due to intravascular haemolysis and tissues damage; CD163 represents a highly efficient system to remove potentially toxic an pro inflammatory hemoglobin from the circulation and local sites of inflammation; for this reason is considered to be a prognostic marker in different diseases; mainly in inflammation (15).…”
Section: Soluble Form Of Cd163 (Scd163)mentioning
confidence: 99%
“…Randomized comparisons between CCABG and OPCAB shows the CCABG patients to have increased serum-levels of a multitude of different substances including tumor necrosis factor-alpha, interleukins 6 and 8, selectin, c-reactive protein, intracellular adhesion molecule -1, and vascular endothelial growth factor (39,(67)(68)(69)(70)(71)(72). Also, the expression of a scavenger molecule on monocytes is significantly higher in "on-pump" patients (73). It has been proposed that this inflammatory over-activation can be harmful and lead to organ failure and infections.…”
Section: Inflammatory Responsementioning
confidence: 99%